Facial asymmetry revisited: Part II–Conceptualizing the management - Dhirendra Srivastava; Harpreet Singh; Sonal Mishra; Poonam Sharma; Pranav Kapoor; Lokesh Chandra (Journal of Oral Biology and Craniofacial Research)
Management of facial asymmetry is one of the arduous and challenging task to accomplish in disciplines of orthodontics and maxillofacial surgery. This article aims to describe various treatment modalities adopted conjointly by the orthodontist and maxillofacial surgeon, taking into consideration the realistic concerns and expectations of the patient. This would help improve treatment outcomes while ensuring overall well-being of the patient.